The Power of Questioning Strategy on Students Learning English in the Classroom - Sujariati Sujariati (BATARA DIDI : English Language Journal, 2022)
The goals of this study were to determine the types of questioning strategies used in the classroom and the impact such strategies have on students' acquisition of English. The kids of senior high school participated in this study as the topic. A qualitative methodology was used for the study that was carried out here. The research included in this study collects data via observation, questionnaires, and interviews. The data that were acquired were then examined by first lowering the amount of data, then displaying the data, and finally deriving conclusions from the data. The results of the investigation revealed that the instructor had used several techniques and methods while questioning the students. These included putting more emphasis on the questions, translating the questions into Bahasa Indonesia, repeating the questions, and moving closer to the students. in addition, the sorts of questions that were used were open/close questions, recall questions, rhetorical questions, and yes/no questions. The instructor was responsible for using these types of questions throughout each individual teaching session. It is dependent on the content that the instructor conveyed to the students as to whether open-ended or closed-ended questions or display questions were the most common. Aside from that, the instructor will only utilize the recall and referential questions a limited number of times. The findings of the study demonstrated that there were positive benefits from using the method and the sorts of questions, namely, favourable answers from students and excellent relationships between the instructor and the students.